Exclusion and zero-range in the rarefaction fan - Gonçalves, Patrícia (2014)
In these notes we briefly review asymptotic results for the totally asymmetric simple exclusion process and the totally asymmetric constant-rate zero-range process, in the presence of particles with different priorities. We review the Law of Large Numbers for a second class particle added to those systems and we present the proof of crossing probabilities for a second and a third class particles. This is done, for the exclusion process, by means of a particle-hole symmetry argument, while for the zero-range process it is a consequence of a coupling argument.